2005
DOI: 10.1128/aem.71.10.5823-5827.2005
|View full text |Cite
|
Sign up to set email alerts
|

Use of Random and Saturation Mutageneses To Improve the Properties of Thermus aquaticus Amylomaltase for Efficient Production of Cycloamyloses

Abstract: Amylomaltase from Thermus aquaticus catalyzes intramolecular transglycosylation of ␣-1,4 glucans to produce cyclic ␣-1,4 glucans (cycloamyloses) with degrees of polymerization of 22 and higher. Although the amylomaltase mainly catalyzes the transglycosylation reaction, it also has weak hydrolytic activity, which results in a reduction in the yield of the cycloamyloses. In order to obtain amylomaltase with less hydrolytic activity, random mutagenesis was perfromed for the enzyme gene. Tyr54 (Y54) was identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
3
29
0
Order By: Relevance
“…This suggests that a yield of LR-CDs with a high degree of polymerization would be improved if only the coupling reaction was inhibited. Fujii et al made amylomaltase mutants by introducing random mutations into the gene coding for this enzyme as proof (71,72). In 2002, it was found that glycogen debranching enzyme (GDE, EC 2.4.1.25/EC 3.2.1.33) from Saccharomyces cerevisiae was also able to produce a LR-CD mixture (73).…”
Section: E Preparation Of Lr-cdsmentioning
confidence: 99%
“…This suggests that a yield of LR-CDs with a high degree of polymerization would be improved if only the coupling reaction was inhibited. Fujii et al made amylomaltase mutants by introducing random mutations into the gene coding for this enzyme as proof (71,72). In 2002, it was found that glycogen debranching enzyme (GDE, EC 2.4.1.25/EC 3.2.1.33) from Saccharomyces cerevisiae was also able to produce a LR-CD mixture (73).…”
Section: E Preparation Of Lr-cdsmentioning
confidence: 99%
“…This second binding site was proposed to help form a CA by the hydrophobic interaction of Tyr-54 and Tyr-101 with the substrate (37). The mutation of these residues affected the hydrolysis activity of the TaAM enzyme, which played an important role in product formation (8,9). A novel AM from the mesophilic bacterium Corynebacterium glutamicum ATCC 13032 (CgAM) has recently been reported, and interestingly, it has only a 28% amino acid sequence similarity to TaAM (36).…”
mentioning
confidence: 99%
“…Although the thermostability was high enough to be used for the industrial scale, the yield of cycloamylose using Thermus aquaticus (Taq) amylomaltase decreased to 60% at the end point of the reaction since the enzyme significantly exhibited hydrolytic activity. 47,48) In such a case, we have two ways to overcome the problems. One is enhancing the thermostability of potato D enzyme, and the other is erasing the hydrolytic activity of Taq amylomaltase.…”
mentioning
confidence: 99%
“…Indeed, we successfully enhanced the thermostability of potato type L α glucan phosphorylase 49) and Streptococcus sucrose phosphorylase. 50) We chose the latter strategy for Taq amylomaltase 47,48) (Fig. 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation